Gender-Based Service Quality Evaluation of Multimodal Public Transportation in DKI Jakarta - Owais, Mohammad; Sumabrata, Jachrizal; Yusuf, Nahry (UI Scholars Hub, 2024)
In DKI Jakarta, despite the extensive infrastructure development, there has been a significant decline in the usage of public transportation. This can be attributed to the inadequate quality of the services provided. Various studies have highlighted the significance of evaluating the quality of service in public transportation to ensure passenger satisfaction and attract new users. However, there is no agreement on the most effective methodology and suitable indicators for conducting such analyses. In addition, there is a growing recognition of the importance of promoting gender equality in multimodal public transportation (MMPT) and understanding gender differences and perceptions of MMPT services. A case study was carried out in DKI Jakarta, the capital of Indonesia, to analyse the influential indicators of the quality of MMPT. The analysis used the Importance Performance Analysis (IPA) combined with the Tarrant and Smith procedure. These indicators greatly impact the perception of MMPT services for both genders. Safety against crimes, facilities for disabled people, pregnant women, and senior citizens, announcements in the required language, clarity in travel-related information, and availability of seats inside vehicles are the most influential indicators of the quality of the services. However, there are significant differences in how women and men perceive the importance and performance of indicators related to seating availability, coordination between transport operators, and passenger information.